EFEKTIFITAS GAMIFICATION BERBASIS BLENDED LEARNING PADA MATA KULIAH PENDIDIKAN EKONOMI - Anwar, Saiful; Marlena, Novi; Wulandari, Retno (UNIVERSITAS NEGERI SURABAYA, 2018)
The purpose of the study is to see the effectiveness of the concept of gamification that is applied in the learning process of the subject of Renewal of Economic Education Learning. The approach used in this study is a qualitative approach. Subjects in this study are students of class 06PIEE001 FKIP Pamulang University. In this study adopted Marczewski's Gamification Framework concept which consists of 8 questions: 1) what is being gamified; 2) why is it being gamified; 3) who are the users; 4) how is it being gamified; 5) analytics are set up; 6) tested with users; 7) acted on feedback; and 8) released the solution. Based on the results of data analysis and discussion, it can be concluded that 1) the learning process in the course of Renewal of Economic Education Learning can be done with the concept of gamification by combining face-to-face learning in the classroom with online learning learning; 2) student response in learning process with gamification concept mostly interested because it is new for them; 3) there is a nurturant effect for as long as the concept of gamification is applied in the class